2022
DOI: 10.1002/vms3.887
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Akabane virus in Taiwan

Abstract: Background Akabane virus (AKAV) is a teratogenic and neuropathogenic arbovirus that infects livestock and wild animals. AKAVs are endemic arboviruses from dairy farms in Taiwan in 1989, and the first sequence was detected in cattle with nonsuppurative encephalitis in 1992. Objectives This study aims to understand the epidemiological relationships of the akabane viruses between Taiwan and nearby places. Methods In this study, 17 specimens were identified or isolated from vector insects, and ruminant fetuses col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This might be especially important for ecological interactions of Culicoides -borne diseases between Taiwan and nearby islands. Studies of BEFV and AKAV showed the possibility of transboundary transmission by Culicoides -borne diseases that could communicate in both directions between Taiwan and the Yaeyama Islands using meteorological analysis, surveillance, and phylogenetic evidence ( Hayama et al 2016 , Tzeng et al 2019 , 2022 ). However, the identification of transboundary events requires information exchange to link the spatiotemporal and phylogenetic relationships between 2 or more epidemic events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be especially important for ecological interactions of Culicoides -borne diseases between Taiwan and nearby islands. Studies of BEFV and AKAV showed the possibility of transboundary transmission by Culicoides -borne diseases that could communicate in both directions between Taiwan and the Yaeyama Islands using meteorological analysis, surveillance, and phylogenetic evidence ( Hayama et al 2016 , Tzeng et al 2019 , 2022 ). However, the identification of transboundary events requires information exchange to link the spatiotemporal and phylogenetic relationships between 2 or more epidemic events.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is an important mechanism for the transboundary movement of Culicoides -borne viruses onto an island such as Taiwan. BEFV and Akabane virus (AKAV, Peribunyaviridae : Orthobunyavirus ) have been reported to be exchanged between Taiwan and nearby localities ( Lee 2019 , Tzeng et al 2022 ), which indicated that the candidate virus list for Taiwan surveillance could be expanded by including surveillance results from nearby localities, such as the Yaeyama Islands and the southeastern part of China. Currently, 7 viruses have been only identified in Taiwan ( Tzeng et al 2019 , Yanase et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…AD has emerged as a common infection among many domestic and wild animals in many Asian nations, including Japan [14], South Korea [15], Taiwan [16], Iraq [17], and China, where it is one of the seven pandemic diseases that are subject to a mandatory quarantine, and prohibits the importation of cattle, sheep, and goats [18]. It has been also reported in a number of countries in the Middle East [19], and Australia [20].…”
Section: Introductionmentioning
confidence: 99%